RELEVANSI NILAI LABA, NILAI BUKU EKUITAS, ARUS KAS OPERASI DAN DIVIDEN - Yulianni Yulianni; Sugi Suhartono (Jurnal Akuntansi, 2019)
The relevance of the value of accounting information presented must have the ability to explain the value of a company. Accounting information in the form of financial statements is said to be relevant if the information can be useful for investors in making decisions and the reaction of investors when information is announced that can be observed through stock price movements because stock prices reflect the value of the company. The theories used in this study are the theory of clean surplus, signaling theory, and theory of market efficiency. Based on the purposive sampling method obtained as many as 79 companies, with a total of 237 samples. The analysis techniques used are pooling test, classic assumption test, descriptive statistical test, F test, t-test, and test coefficient of determination. The data used is secondary data obtained from www.idx.co.id. The results showed that earnings, equity book values, operating cash flows, and dividends proved to have a positive influence on stock prices.Keywords : Earnings, book value of equity, operating cash flows, dividends, and stock price